Propionibacterium freudenreichii CIRM-BIA 129 Osmoadaptation Coupled to Acid-Adaptation Increases Its Viability During Freeze-Drying - Gaucher, Floriane; Kponouglo, Koffigan; Rabah, Houem; Bonnassie, Sylvie; Ossemond, Jordane; Pottier, Sandrine; Jardin, Julien; Briard-Bion, Valérie; Marchand, Pierre; Blanc, Philippe; Jeantet, Romain; Jan, Gwénaël (Frontiers in Microbiology, 2019)
Propionibacterium freudenreichii is a beneficial bacterium with documented effects on the gut microbiota and on inflammation. Its presence within the animal and human intestinal microbiota was correlated with immunomodulatory effects, mediated by both propionibacterial surface components and by secreted metabolites. It is widely implemented, both in the manufacture of fermented dairy products such as Swiss-type cheeses, and in the production of probiotic food complements, under the form of freeze-dried powders. The bottleneck of this drying process consists in the limited survival of bacteria during drying and storage. Protective pre-treatments have been applied to other bacteria and may, in a strain-dependent manner, confer enhanced resistance. However, very little information was yet published on P. freudenreichii adaptation to freeze-drying. In this report, an immunomodulatory strain of this probiotic bacterium was cultured under hyperosmotic constraint in order to trigger osmoadaptation. This adaptation was then combined with acid or thermal pre-treatment. Such combination led to accumulation of key stress proteins, of intracellular compatible solute glycine betaine, to modulation of the propionibacterial membrane composition, and to enhanced survival upon freeze-drying. This work opens new perspectives for efficient production of live and active probiotic propionibacteria.